2009
DOI: 10.1080/08977190902834077
|View full text |Cite
|
Sign up to set email alerts
|

The antifibrogenic effect of hepatocyte growth factor (HGF) on renal tubular (HK-2) cells is dependent on cell growth

Abstract: Although several reports suggest an antifibrogenic effect of hepatocyte growth factor (HGF), an increased deposition of matrix induced by HGF has also been reported. These conflicting effects could result from a diverse proliferative state of the target cells. Aim of the present study was to evaluate HGF effects on growth arrested (quiescent) and actively proliferating renal tubular epithelial (HK-2) cells. HK-2 cells were cultured in RPMI medium either on agarose gel or on plastic surface in order to inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…It had been demonstrated that HGF increases production of ECM in renal cells [50] and induces profibrotic changes in peritoneal cells [51]. Based on the observation that there is a relationship between cell proliferation and production of ECM molecules [52] and that the effects and expression of growth factors may be altered by ECM components [53], Esposito showed that HGF affects quiescent and proliferating renal tubular epithelial (HK-2) cells differently, favoring deposition of ECM in proliferating and matrix degradation in quiescent HK-2 cells [54]. Clinically, antifibrotic therapy often is initiated without control of the underlying disease process and therefore liver cells would be in a proliferative state.…”
Section: Discussionmentioning
confidence: 99%
“…It had been demonstrated that HGF increases production of ECM in renal cells [50] and induces profibrotic changes in peritoneal cells [51]. Based on the observation that there is a relationship between cell proliferation and production of ECM molecules [52] and that the effects and expression of growth factors may be altered by ECM components [53], Esposito showed that HGF affects quiescent and proliferating renal tubular epithelial (HK-2) cells differently, favoring deposition of ECM in proliferating and matrix degradation in quiescent HK-2 cells [54]. Clinically, antifibrotic therapy often is initiated without control of the underlying disease process and therefore liver cells would be in a proliferative state.…”
Section: Discussionmentioning
confidence: 99%
“…However, Esposito et al . [34] found that HGF acts as anti-fibrotic factor reducing TGF effect only on quiescent renal tubular (HK-2) cells. On proliferating cells, HGF increases TGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Expression has also been reported in proximal tubule cells, but primarily only in response to insults, mitogens, or second messengers (14,20,41,45,62,63). There is a dearth of information regarding IGFBP7 in the kidney, and what is available is contradictory, showing expression in the glomerulus and alternatively in distal and proximal tubule cells (17,35,42,65,72).…”
mentioning
confidence: 94%